Pengembangan intelektual manusia sebagai pencerminan pembentukan karakter - Erma .; Debby Anggraeni (CV. ITTC INDONESIA, 2026)
This study examines the role of intellectual development in shaping human character within the context of modern education. The main issue addressed is the tendency to separate cognitive achievement from moral and ethical formation, potentially leading to intelligent individuals with weak character. The research aims to analyze the relationship between intellectual progress—encompassing critical thinking, problem-solving, and knowledge application—and the cultivation of core character values such as integrity, responsibility, and empathy. Using a qualitative literature review method, this study explores theoretical frameworks and empirical findings from educational psychology and character education. The results indicate that intellectual development, when designed to integrate ethical reflection and social awareness, serves as an effective medium for character building. The process of intellectual inquiry inherently fosters discipline, honesty, and respect for truth, which are fundamental to strong character. The study concludes that a synergistic and intentional approach in education is essential to ensure that intellectual advancement directly contributes to the formation of holistic, ethical character.